Predictive Utility of Alternate Measures of Physical Activity and Diet for Overweight and Obesity in Low-Income Minority Women. Issue 5 (June 2022) - Liu, Ying; Shier, Victoria; King, Sara; Datar, Ashlesha
Purpose: The purpose is to compare the predictive utility of alternate measures of diet and physical activity for overweight and obesity among low-income minority women. Design: Cross-sectional analysis of baseline data from a cohort study. Setting: Three public housing developments in South Los Angeles. Subjects: Adult women (N = 425). Measures: Primary outcome—weight status (normal BMI, overweight, or obese). Primary predictors— diet: 24-hour dietary recalls (Healthy Eating Index), dietary screener (intake of specific food groups), and single-item survey question (diet quality); physical activity: accelerometry (minutes/day of moderate-to-vigorous activity), short recall questionnaire (minutes/week of moderate and vigorous activity), and single-item questions (days per week did exercise; self-assessment of overall activity level). Analysis: Multinomial logistic regression models, controlling for socio-demographic covariates. Models are built up starting with least resource-intensive measures of diet and physical activity (single items) and sequentially adding more resource-intensive measures. Model performance is assessed via information-based model selection indices. Results: Adjusted relative risk for obesity for single-item measures ranged from .61 to .64 for diet ( P < .01) and from .80 to .81 for physical activity (P <.05). The added value of resource-intensive measures was negligible for physical activity and at best small for diet. Conclusion: Single-item questions for diet and physical activity can provide valuable information about risk for overweight and obesity in low-income minority women when more resource-intensive assessments are infeasible.